Utilization of School Library in Supporting Teacher's Professionalism in Teaching at SMK Nurul Musthofa Demak - Mugono, Solikin (2012)
Focus of this study was on what are characteristics of the utilization of school library in supporting teacher's professionalism in teaching at SMK Nurul Musthofa Demak? There were three goals in this study- to describe the characteristics of teachers' professional in planning a learning activity by utilizing school library at SMK Nurul Musthofa Demak; to describe the characteristics of teachers' professional in implementation of learning activity by utilizing school library at SMK Nurul Musthofa Demak; and to describe the characteristics of teachers' professional in evaluation of learning activity by utilizing school library at SMK Nurul Musthofa Demak. It is a qualitative study using ethnography design. The main data were collected from several informants-the principal, teachers and students. The method of data collection was by using observation, in-depth interview, and documentation. Data analysis of this study was an interactive model of analysis. Testing of data validity of this study used credibility, transferability, dependability, and confirmability. This finding suggested that the utilization of school library in supporting teacher's professionalism in teaching covered the process of planning, implementation and evaluation of learning. In planning, the ability to be possessed by a professional teacher was to prepare the instructional programs including lesson plan and syllabus. The utilization of school library in this process was to use references in the library as learning sources to prepare the instructional programs. In the implementation of learning, teacher invited students to come to the library because they have to find material for discussion. Evaluation aimed to know the quality of students in the school and the development of students' ability improvement. Evaluation was used to know whether the standard of competence and the basic competence of instructional material have been achieved or not. There are only two kinds of evaluation at SMK Nurul Musthofa i.e. evaluation during the learning process, and the final evaluation. The evaluation at SMK Nurul Musthofa when the learning process occurred was done by giving a quizzes, assignment, observation and asking the students about the lesson being presented. The final evaluation was in a task whether it must be finished on that day or collected in the next meeting.